Fenologia, produção e qualidade de frutos da goiabeira ‘Paluma’ em diferentes épocas de poda - da Silva, Marlon Jocimar Rodrigues [UNESP]; Tecchio, Marco Antonio [UNESP]; Domiciano, Sofia [UNESP]; Leonel, Sarita [UNESP]; Balestrero, Rodrigo Issa [UNESP] (FapUNIFESP (SciELO), 2016)
Pruning guava trees at different times is an important management tool that allows year-long staggering of fruit production. In this context, this study aimed to evaluate the phenological characteristics, yield and fruit quality of the ‘Paluma’ guava tree at different pruning times in Botucatu, SP. The study used a completely randomized design with four treatments, four replicates and a useful experimental plot plant. The treatments consisted of four different pruning times, August 27, September 11, September 26 and October 11. The following phenological phases were evaluated: branch establishment, flowering, early fruiting, fruit ripening and harvesting. It was determined the number of flower buds, fixed fruits and fixation index fruit were determined. The fruit growth curve was obtained by measuring the transverse and longitudinal diameter. At the time of harvest, the number of fruits per plant, yield and productivity were measured. In the harvested fruits, the fresh mass, the transverse and longitudinal diameter, the flesh and core thickness, the flesh and core mass, soluble solids, titratable acidity and pH were determined. The ‘Paluma’ guava trees pruned in August showed higher phenological stage durations than the other pruning times; however, those pruned in early September showed higher fixation index fruit, fruit yield and better physical characteristics. The guava trees pruned in August showed lower titratable acidity values and higher soluble solids/titratable acidity ratio.
Phenology, yield and fruit quality of ‘Paluma’ guava tree at different pruning times
Keywords: Fixation index; Fruit growth; Fruit set; Psidium guajava L